The relevance of the meat value chain analysis to reducing malnutrition in developing countries: a systematic literature review - Purnamasari, Endah; Scollan, Nigel; Bozzola, Martina (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
This study examines the evidence from the literature relevant to analysing the meat value chain and its relevance in reducing the prevalence of malnutrition in developing countries. A systematic literature review was performed to synthesise a qualitative evidence base, including information on the study country, time frame, methodology, research question, sample population, limitations, and recommendations for future research. The Cochrane methodology was employed to review 46 studies systematically. It was noted that studies are often conducted in multiple countries, mainly in Asia and Africa. The specific period over which the studies were conducted, or the period of data collection or observation, was often less than one year, highlighting significant changes in outcomes after the intervention, for example, increased Fe status. However, interventions are not known to reduce the prevalence of malnutrition directly. Research questions are asked using a variety of methods. Quantitative, qualitative and mixed methods. Quantitative approaches focused on identifying potential risk hotspots, while qualitative research focused on assessing the impact of change. Economic systems and vulnerable groups are often investigated as concerns of developing countries. This study broadens the conceptual framework and demonstrates its potential to contribute to nutritional literacy and the meat industry.Â